Crosstalk with infant-derived Th17 cells, as well as exposure to IL-22 promotes maturation of intestinal epithelial cells in an enteroid model - Sharafian, Zohreh; Littlejohn, Paula T.; Michalski, Christina; Sousa, James A.; Cheung, Janelle; Hill, Mariana; Piper, Hannah; Jacobson, Kevan; Lavoie, Pascal M.; Allaire, Joannie M.; Vallance, Bruce A. (Frontiers in Immunology, 2025)
IntroductionThe intestinal epithelium of human infants is developmentally immature compared to that of adults. Exactly how this immaturity affects key epithelial functions and their interactions with nearby immune cells remains an understudied area of research, partly due to limited access to non-diseased infant gut tissues. Human intestinal organoids, or “mini guts” generated from tissue stem cells, are promising models for investigating intestinal biology and disease mechanisms. These three-dimensional structures closely mimic their tissue of origin, including cellular physiology and genetics. We have also previously shown that neonatal Th17 cells represent a distinct cell population with a cytokine profile skewed toward IL-22 production rather than IL-17A, as seen in adult Th17 cells.MethodsIn this study, we sought to model the impact of neonatal-derived Th17 cytokine, namely IL-22 and the intestinal epithelium using infant-derived ileal enteroids. We generated enteroids from ileal biopsies from infants (< 6 months old) and cultured them for seven days with standard organoid growth media, organoid media supplemented with conditioned media from cord-blood-derived Th17 cells, or media supplemented with recombinant IL-22. We assessed morphological changes and conducted transcriptomics profiling via RNAseq.ResultsExposing enteroids to neonatal Th17-cells-derived conditioned media led to enhanced growth, maturation, and differentiation as compared to control media. These effects were ablated when an IL-22 neutralizing antibody was used, while conversely, supplementing with recombinant IL-22 mimicked the Th17 effects, increasing intestinal epithelial cell proliferation and inducing marked differentiation of secretory cells. Our transcriptomic profiling similarly demonstrated significant changes in response to IL-22 with downregulation of Wnt and Notch signaling and upregulation of immune pathways, particularly interferon signaling. The transcriptomic data also suggested that IL-22 treatment led to changes in cell type composition with an increase in stem- and progenitor cells at the expense of enterocytes.ConclusionTaken together, our data suggests that early-life intestinal development is likely influenced by IL-22-dependent crosstalk between the infant epithelium and exposure to neighboring Th17 cells. This promotes epithelial cell maturation and immune readiness, reflected at both the morphological and molecular levels. Our work also provides a relevant framework for studying healthy infant gut development, which can be further leveraged to examine early-life gastrointestinal disorders, model complex human disease, and therapeutic testing while reducing reliance on animal models.